THE IMPACT OF WORK-LIFE BALANCE AND WORKLOAD ON TURNOVER INTENTION BY MEDIATING WORK STRESS AT THE CLASS I IMMIGRATION OFFICE OF TPI JAMBI - Andrianto Piro Ndoda; Megawaty Megawaty; Maryam Nurdin (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
This study aims to analyze the influence of work-life balance and workload on turnover intention, with work stress as a mediating variable among employees of the Class I Immigration Office at the Jambi TPI. The study used a quantitative approach with a causal associative research design. The study population was 150 employees, and the entire population was sampled using a saturated sampling technique. Data collection was conducted through questionnaires using a five-point Likert scale. Data analysis used the Structural Equation Modeling-Partial Least Squares (SEM-PLS) with the help of the SmartPLS 4 application. The results of the study indicate that work-life balance has a negative and significant effect on work stress, while workload has a positive and significant effect on work stress. In addition, work-life balance has a negative and significant effect on turnover intention, while workload and work stress have a positive and significant effect on turnover intention. The mediation effect test shows that work stress mediates the effect of work-life balance on turnover intention, as well as the effect of workload on turnover intention. These findings indicate that improving work-life balance can reduce work stress and reduce the tendency of employees to leave the organization. Conversely, a high workload increases work stress, which ultimately increases turnover intention. The results of this study are expected to serve as a basis for the Class I TPI Jambi Immigration Office in formulating human resource management policies by improving work-life balance, regulating proportional workloads, and controlling work stress to increase employee loyalty and the sustainability of the quality of public services.